If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2p-6)(7p+4)(p-8)=0
We multiply parentheses ..
(+14p^2+8p-42p-24)(p-8)=0
| 7p-8=8p-17 | | 4z/10-4=-3 | | f-975=-409 | | p+3=8.25 | | 3p=8.25 | | 5v+3v+v-3v=12 | | t+218=663 | | 6w=72w= | | 2c=35 | | p-710=-168 | | 6y−9=63 | | 5v+3v+v−3v=12 | | 12-3/4x=18-3x | | -13h=585 | | x/10+7=-2 | | 6/b=5 | | –8c+11c+–20c−–14c−–16c=13 | | 15n=540 | | 4+2q=-18 | | -14=c+33 | | -2/3×d=-4/5 | | -12=-8+r | | q+-308=-568 | | k-409=104 | | 18b-17b=7 | | q-558=-103 | | 12v−5=17v−18−4v | | r+-103=-995 | | -8+4u=20 | | 9=j-3 | | 6j-4j=8 | | x2+29=4x |